SBRT and HDR brachytherapy produce lower PSA nadirs and different PSA decay patterns than conventionally fractionated IMRT in patients with low- or intermediate-risk prostate cancer - Kishan, Amar; Wang, Pin-Chieh; Upadhyaya, Shrinivasa K.; Hauswald, Henrik; Demanes, D. Jeffrey; Nickols, Nicholas G.; Kamrava, Mitchell; Sadeghi, Ahmad; Kupelian, Patrick A.; Steinberg, Michael L.; Prionas, Nicolas D.; Buyyounouski, Mark K.; et al. (Practical Radiation Oncology, 2016)
To compare patterns of prostate-specific antigen (PSA) response following stereotactic body radiation therapy (SBRT), high-dose-rate (HDR) brachytherapy, and conventionally fractionated intensity modulated radiation therapy (IMRT) in patients with low- or intermediate-risk prostate cancer (CaP).